Korelasi Jumlah Beban yang Diangkat dengan Tingkat Kelelahan pada Buruh di Gudang Bulog Dasan Cermen Mataram - Mulya Tarmidi (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2017)
Every worker lift burden differently due to physical condition and age of the workers so the researchers wanted to see whether there was a correlation between the  amount of weight lifted with the level of fatigue of the workers. The research purposes was to identify the correlation be- tween the amount of weight lifted and the level of fatigue in workers in the warehouse Bulog Dasan Cermen Mataram 2015. This research was analytic survey research, Cross Sectional want to raise the amount of weight lifted relationship with the level of fatigue of the worker carried out once the observations within a specified period or one time. The study population was all worker of Bulog Warehouse as many as 35 people. Based on the test tool Pearson Chi-Square was obtained was obtained p = 0.005 <a 0.05 (significant). The total Weight Appointed With Fatigue Level Workers In Bulog Warehouse At Dasan Cermen Mataram had significant correlation. With the value of the odds ratio = 7.778, which meant someone who had a heavy burden had seven times greater risk of causing fatigue.